2017
DOI: 10.1007/s11701-017-0681-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous robotic subtotal gastrectomy and right hemicolectomy for synchronous adenocarcinoma of stomach and colon

Abstract: Simultaneous laparoscopy-assisted resection for synchronous stomach and colon cancers has been reported frequently; however, robot-assisted gastrectomy and colectomy for these conditions are rarely reported. We report the successful use of robotic surgery for synchronous cancers of the stomach and colon. A 71-year-old woman with no specific medical history was diagnosed with early gastric cancer at the gastric angle and right colon cancer after undergoing esophagogastroduodenoscopy and colonofiberoscopy. Abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…A long midline incision would have been inevitable if we could not proceed with the laparoscopic technique for gastrectomy and colectomy. This type of incision could lead to many complications, such as increased postoperative pain, reduced ambulation, and increased length of postoperative hospital stay [16]. Laparoscopic surgery has recently become a popular option and has been gradually replacing conventional open surgery in several elds of abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A long midline incision would have been inevitable if we could not proceed with the laparoscopic technique for gastrectomy and colectomy. This type of incision could lead to many complications, such as increased postoperative pain, reduced ambulation, and increased length of postoperative hospital stay [16]. Laparoscopic surgery has recently become a popular option and has been gradually replacing conventional open surgery in several elds of abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A long midline incision would have been inevitable if we could not proceed with the laparoscopic technique for gastrectomy and colectomy. This type of incision could lead to several complications, such as increased postoperative pain, reduced ambulation, and increased length of postoperative hospital stay [17]. Laparoscopic surgery has recently become a popular option and has been gradually replacing the conventional open surgery in several fields of abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the operative time was long. In previous reports, the operative time of the simultaneous robotic surgery for GC and RC was 640 min [12], and in this Fig. 5 Operating room settings.…”
Section: Discussionmentioning
confidence: 58%
“…Although there are some reports on simultaneous laparoscopic surgery for synchronous GC and CRC [ 8 11 ], this is the first report on simultaneous total robotic curative resection for synchronous advanced GCs and RCs. Byoung et al first reported simultaneous robotic surgery for GC and right colon cancer [ 12 ]. Although both GC and CRC were advanced cancers in this case, robotic surgery had advantages for both peripancreatic lymph node dissection for GC surgery [ 13 , 14 ] and pelvic manipulation (especially to reduce neuropathy and urinary retention) for RC surgery [ 4 , 15 ] and was therefore selected to reduce postoperative complications and allow for a smooth introduction of postoperative chemotherapy for GC.…”
Section: Discussionmentioning
confidence: 99%